Circle of fire : Dickens' vision & style & the popular Victorian theater - Axton, William F. (Lexington : The University Press of Kentucky, 2015)
This study explores the theater actually known and frequented by Dickens in order to show in terms of concrete structural analysis of his novels the nature of the predominantly ""dramatic"" or ""theatrical"" quality of his genius. Author William F. Axton finds that the three principal dramatic modes or ""voices"" that were characteristically Victorian were burlesquerie, grotesquerie, and the melodramatic, and that the novelist's vision of the world around him was drawn from ways of seeing transformed from those elements in the popular playhouse of his day -- as revealed in the structure and th
APPENDIX A: An Evening at a Victorian PlayhouseAPPENDIX B: The News of Nemo's Death Reaches Cook's Court; NOTES; INDEX; A; B; C; D; E; F; G; H; J; L; M; N; O; P; R; S; T; V; W; Z.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Dickens, Charles, -- 1812-1870 -- Knowledge -- Performing arts; Dickens, Charles, -- 1812-1870; Theater -- Great Britain -- History -- 19th century; Great Britain -- History -- Victoria, 1837-1901.; Performing arts in literature; Théâtre -- Grande-Bretagne -- Histoire -- 19e siècle.; Grande-Bretagne -- Histoire -- 1837-1901 (Victoria); Arts du spectacle dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Performing arts; Performing arts in literature; Theater; Great Britain; 1800-1901; History